LEARNING MOTIVATION AND ITS RELATIONSHIP WITH RECEIVING AWARDS AND STUDENTS’ PERFORMANCE IN AN ACADEMIC ENVIRONMENT - Elitsa Petrova (Defence Science Review, 2017)
The article presents a research on learning motivation and its relationship with receiving awards and better students’ performance in an academic environment. The article includes an analysis of the results of a research conducted at the National Military University of the Republic of Bulgaria. It develops more thoroughly the author’s previous studies on the motivation of civilian and military students, focusing on the influence of positive reinforcements on motivation for education and military training and the influence of positive reinforcements on the motivation of cadets in the training process and its relation with performance at the university. The object of the study is cadets in the last year of their education in the Military Science professional field, specialising in Organisation and Management of Military Units at a Tactical Level at the National Military University in Bulgaria, as well students and cadets in the first year of education are included as control groups for comparison.